Core functionalization of semi-crystalline polymeric cylindrical nanoparticles using photo-initiated thiol–ene radical reactions. Issue 13 (25th February 2016) - Sun, Liang; Pitto-Barry, Anaïs; Thomas, Anthony W.; Inam, Maria; Doncom, Kay; Dove, Andrew P.; O'Reilly, Rachel K.
Abstract : Functionalisation by radical thiol–ene addition of a cylindrical micelle formed by crystallisation-driven self-assembly is demonstrated. Abstract : Sequential ring-opening and reversible addition–fragmentation chain transfer (RAFT) polymerization was used to form a triblock copolymer of tetrahydropyran acrylate (THPA), 5-methyl-5-allyloxycarbonyl-1, 3-dioxan-2-one (MAC) andl -lactide. Concurrent deprotection of the THPA block and crystallization-driven self-assembly (CDSA) was undertaken and allowed for the formation of cylindrical micelles bearing allyl handles in a short outer core segment. These handles were further functionalized by different thiols using photo-initiated thiol–ene radical reactions to demonstrate that the incorporation of an amorphous PMAC block within the core does not disrupt CDSA and can be used to load the cylindrical nanoparticles with cargo.